Optimizing Romaine Lettuce Plant Yield and Growth by Providing Liquid Organic Fertilizer from Rabbit Urine - Ilham Tri Saputra; Andriani Eko Prihatiningrum (CV. Media Digital Publikasi Indonesia, 2025)
This study aims to determine the effect of liquid organic fertilizer (POC) made from rabbit urine as a source of N, P, and K nutrients and the interval of POC administration on the growth and yield of romaine lettuce plants. The study was conducted in the experimental field of Muhammadiyah University of Sidoarjo, Modong Village, Tulangan District, using a Randomized Block Design (RAK) with 9 treatments and 3 replications (27 experimental units). The first factor was the concentration of rabbit urine POC (20 ml/L, 40 ml/L, and 60 ml/L), and the second factor was the administration interval (once every 2, 4, and 6 days). The parameters observed included plant height, number of leaves, root length, wet weight, and dry weight. The results showed that the 60 ml/L treatment with an interval of once every 4 days (K312) gave the best results in the number of leaves, wet weight, and dry weight. However, plant height and root length showed no significant results in the treatment interaction.